Semantic Roles of English Language Teaching Derivational Suffixes - Kamal, Rusul Neima; Jrew, Raqib Abbas; Al-Rikabi, Estabraq Waleed Attwan; Mohammed, Aqeel Muslim (Manar Elsharq Journal for Literature and Language Studies, 2025)
The purpose of this study is to describe the roles of the suffixes in English and to identify similarities and contrasts in the semantic functions of suffixes in the English language. Descriptive qualitative research and linguistic approach were the methods employed in this study. The findings of this study show that: (1) English suffixes follow the stem and create a new derivative in a different part of speech or word by altering the lexico-grammatical meaning of the word; and (2) There are four different kinds of suffixes in English: nominal, verbal, adjective, and adverbial.